New records of invasive insects (Hemiptera: Sternorrhyncha) in Southeast Asia and West Africa - Muniappan, R.; Shepard, B.; Watson, G.; Carner, G.; Rauf, A.; Sartiami, D.; Hidayat, P.; Afun, J.V.; Goergen, Georg E.; Ziaur Rahman, A.K. (South Carolina Entomological Society, 2009)
Several sap-sucking insects (Hemiptera: Sternorrhyncha) of neotropical origin have been accidentally introduced to Southeast Asia and West Africa in recent years, including the mealybugs Paracoccus marginatus Williams & Granara de Willink, Phenacoccus madeirensis Green, Phenacoccus manihoti Matile-Ferrero, Phenacoccus solenopsis Tinsley, Pseudococcus jackbeardsleyi Gimpel & Miller, and the whitefly Aleurodicus dugesii Cockerell (Aleyrodidae). This paper documents new distribution records of introduced mealybugs and some other sap-sucking hemipteran insects (Coccidae and Diaspididae) in these regions and discusses progress in the biological control of some of these pests.